Relationship between Nomophobia, Various Emotional Difficulties, and Distress Factors among Students - Lea Santl; Lovorka Brajkovic; Vanja Kopilaš (MDPI AG, 2022)
The concept of nomophobia is a relatively new and is defined as the fear of not being able to use all the features and benefits provided by smartphones. The main goal of this research was to examine the relationship between nomophobia and various emotional difficulties and distress factors. The following measuring instruments were used on a sample of 257 Croatian students whose average age was 22 years: Nomophobia Questionnaire (NMP-Q); Scales of Depression, Anxiety, and Stress (DASS); Social and Emotional Loneliness Scale (SELSA); and Emotional Skills and Competences Questionnaire (ESCQ-15). Significant correlations between nomophobia and all examined variables were determined. It was found that nomophobia and emotional skills and competence act as significant predictors in expression of distress factors: 30% of the variance in the severity of depression symptoms, 24% of the variance in the severity of anxiety symptoms, and 26% of the variance in the severity of stress symptoms were explained.